ASSESSMENT OF HEAVY METAL CONCENTRATIONS IN IARA RIVER BASIN, CLUJ COUNTY, ROMANIA - ABĂNĂRIȚEI, Iuliana-Andreea; BĂTINAȘ, Răzvan-Horațiu (Studia Universitatis Babeș-Bolyai Geographia, 2025)
This study focuses on the results of analyses carried out on water samples collected in December 2024 and analyzed at the Research Institute for Analytical Instrumentation in Cluj-Napoca. The samples in question were taken within the perimeter of the Iara River basin, which was an important hub for the extractive industry during the communist regime in Romania. With the halting of many industrial and mining activities, mining infrastructure elements were abandoned, posing a significant pollution risk. In the case of the study area, these infrastructure elements are represented by residual waste dumps. However, the results of the water samples reflect not only a very low concentration of heavy metals, but also a very good example of water quality administration and management.